A facile one-step synthesis of porous N-doped carbon from MOF for efficient thermal energy storage capacity of shape-stabilized phase change materials. (June 2019) - Atinafu, Dimberu G.; Dong, Wenjun; Hou, Changmin; Andriamitantsoa, Radoelizo S.; Wang, Jingjing; Huang, Xiubing; Gao, Hongyi; Wang, Ge
Abstract: N-doped porous carbon (NPC-Al) synthesized using one step process of NH2 -MIL-53(Al) metal organic framework was used to prepare polyethylene glycol (PEG)-based composite phase change materials (PCMs). NPC-Al exhibited large and regular pore dimension, large specific surface area (2193.5 m 2 /g), high mesopore proportion, high nitrogen content and chemically tunable material, which are difficult for post-synthesis driven N-doped porous carbons and raw carbons, and taken as a potential candidate for storage applications. Importantly, the effect of nitrogen on PCM loading, thermal conductivity, energy storage and efficiency was systematically studied. NPC-Al exhibited homogeneous PEG loading capacity (up to 90 wt%), improved thermal conductivity up to 52% and thermal storage capability (reach to 100.3%) in a melting enthalpy of 168.3 J/g, 47.2% higher than that of un-doped carbon derived from the same process due to porous characteristics and additional interaction presented between nitrogen atoms along with flexible original metal organic framework material. In addition, the composites exhibited excellent durability up to 99.5% retention after 50-times thermal cycling performance without leakage, better thermal effusivity and specific heat capacity than pristine PEG, which can realize to use for efficient building energy applications. Graphical abstract: A mesoporous N-doped carbon was used to prepare novel shape-stabilized PEG@NPC-Al composites with high energy storage capacity.Image 1 Highlights: High surface area mesoporous N-doped porous carbon were prepared. 90 wt% PEG was encapsulated in NPC-Al. The composite PCMs achieved a heating enthalpy of 168.3 J/g. The storage capacity reaches to 100.3% with 99.5% retention after 50 times cycling. The composite attained improved thermal conductivity and thermal effusivity.